1987
DOI: 10.1098/rstb.1987.0037
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oily discharges on the meiobenthos of the North Sea

Abstract: The impact of hydrocarbon discharges on the intertidal and subtidal meiobenthos of the North Sea is examined primarily by a consideration of two field investigations. The first study examines the effects of an oil refinery discharge on intertidal meiofauna in the Firth of Forth, while the second describes the impact of oil platform discharges on the surrounding meiobenthos. The impact of the refinery effluent is only clearly distinguishable upstream of the discharge, as downstream the effects are confused with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…This result is probably an opportunistic response from some epibenthic copepods, able to tolerate barium, and colonize drill cutting deposits with low TPH. Moore et al (1987) also observed a similar response near a drilling platform in North Sea, where the abundance of copepods was either unaffected or significantly increased, suggesting that living copepod species flourished in more oxygenated conditions where bacteria levels are enhanced and predation pressure reduced. Similarly, experiments with copepods and nematode assemblages in microcosms dosed with different toxicity levels of oil-based drill cuttings showed a markedly increase of copepods in all low-toxicity treatments (Leaver et al 1987).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…This result is probably an opportunistic response from some epibenthic copepods, able to tolerate barium, and colonize drill cutting deposits with low TPH. Moore et al (1987) also observed a similar response near a drilling platform in North Sea, where the abundance of copepods was either unaffected or significantly increased, suggesting that living copepod species flourished in more oxygenated conditions where bacteria levels are enhanced and predation pressure reduced. Similarly, experiments with copepods and nematode assemblages in microcosms dosed with different toxicity levels of oil-based drill cuttings showed a markedly increase of copepods in all low-toxicity treatments (Leaver et al 1987).…”
Section: Discussionsupporting
confidence: 56%
“…Due to their ubiquitous distribution in nature, high abundance and diversity, intimate association with sediments, fast reproduction, and rapid life histories, meiofauna are widely regarded as ideal organisms to study the potential ecological effects of natural and anthropogenic impacts (reviewed by Coull and Chandler 1992). Despite this, information on the effects of cutting discharge on meiofauna community structure at lower taxonomic levels (e.g., genus composition) is, to our knowledge, limited to one study along the banks of an estuary in the North Sea, where the fluid used was mineral oil (Moore et al 1987) and another at the slope of SW Atlantic, drilled with paraffin-based NAF type III (Netto et al 2009). Also, most previous studies have so far reported on the impact of oilbased fluids (Olsgard and Gray 1995;Moore et al 1987) which toxicity is known to be much higher than water-based fluids (Neff et al 2000).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Macrofaunal colonization did not seem to be affected by oil concentrations up to 600 ppm, and increasing oil concentrations above 1 000 ppm led to reduced densities of most species. Some field and experimental studies indicate that oil concentrations of about 2 000 ppm in sediments is 182 the level where detrimental effects begin (DICKS & HARTLEY 1982;DECKER & FLEEGER 1984;MOORE & al. 1987).…”
Section: Discussionmentioning
confidence: 97%